HUBUNGAN KESTABILAN EMOSI DENGAN PENGELOLAAN DIRI SISWA - Satriadi, M.; Nuraeni, Nuraeni; Najamuddin, M. (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2024)
ABSTRACT Emotional stability is an important aspect of adolescent development that influences an individual’s ability to self-regulate in both academic and social contexts. At the junior high school level, adolescents often experience emotional instability that may affect their self-management abilities, such as behavior control, decision-making, and adaptation to environmental demands. This condition highlights the importance of examining the relationship between emotional stability and students’ self-management. This study aims to determine the relationship between emotional stability and self-management among Grade VIII students of SMPN 4 Lingsar in the 2020/2021 academic year. This study employed a quantitative approach with an ex post facto correlational design. The population consisted of all Grade VIII students of SMPN 4 Lingsar (N = 100 students), while the sample comprised 50 students selected using proportional random sampling. The instrument used was a Likert-scale questionnaire developed based on the dimensions of emotional stability (Azwar, 2010) and self-management (Goleman in Rinanda, 2006). Validity was tested using Pearson Product Moment correlation, and reliability was measured using Cronbach’s Alpha formula. Data were analyzed using Pearson Product Moment correlation analysis. The results showed that r-count = 0.567 > r-table = 0.281 at a 5% significance level with df = 49. The null hypothesis was rejected, indicating a positive and significant relationship between emotional stability and students’ self-management. It can be concluded that the higher the students’ emotional stability, the better their self-management ability. ABSTRAK Kestabilan emosi merupakan salah satu aspek penting dalam perkembangan remaja yang berpengaruh terhadap kemampuan individu dalam mengelola diri, baik dalam aspek akademik maupun sosial. Pada usia sekolah menengah pertama, remaja sering mengalami ketidakstabilan emosi yang dapat berdampak pada kurang optimalnya pengelolaan diri, seperti pengendalian perilaku, pengambilan keputusan, dan penyesuaian terhadap tuntutan lingkungan. Kondisi ini menunjukkan pentingnya kajian mengenai hubungan antara kestabilan emosi dan pengelolaan diri siswa. Penelitian ini bertujuan untuk mengetahui hubungan antara kestabilan emosi dengan pengelolaan diri siswa kelas VIII SMPN 4 Lingsar Tahun Pelajaran 2020/2021. Penelitian menggunakan pendekatan kuantitatif dengan desain ex post facto korelasional. Populasi penelitian adalah seluruh siswa kelas VIII SMPN 4 Lingsar (N = 100 siswa) dan sampel berjumlah 50 siswa yang dipilih menggunakan teknik proportional random sampling. Instrumen berupa angket skala Likert yang dikembangkan berdasarkan aspek kestabilan emosi (Azwar, 2010) dan aspek pengelolaan diri (Goleman dalam Rinanda, 2006). Validitas diuji dengan korelasi Product Moment Pearson dan reliabilitas dengan Alpha Cronbach. Teknik analisis data menggunakan korelasi Product Moment Pearson. Hasil analisis menunjukkan rxy hitung = 0,567 > rtabel = 0,281 pada taraf signifikansi 5% dengan df = 49. Hipotesis nol ditolak sehingga disimpulkan terdapat hubungan yang positif dan signifikan antara kestabilan emosi dengan pengelolaan diri siswa. Semakin tinggi kestabilan emosi siswa, semakin baik kemampuan pengelolaan dirinya.